2022
DOI: 10.2147/nrr.s373146
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Nursing Code of Ethics Practice in Gurage Zone, SNNPR, Ethiopia, 2022

Abstract: Ethical codes are a set of systematic binding and guiding rules defining morally acceptable ethical behavior. The nursing profession is the backbone of the medical industry and the front-line healthcare service providers. Nowadays providing ethically competent, compassionate and respectful care is highly essential. Objective: Determining Factors associated with nursing code ethics practice among nurses working in Gurage zone hospitals, 2022. Methods: From February 1 to March 30, 2022, an institution-based cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
(15 reference statements)
1
1
1
Order By: Relevance
“…This study was supported by a study in Gambia (2018) which found that educational level affected the proper practicing code of ethics among nurses (Bah & Sey-Sawo, 2018 However, the current finding was incongruent with the Egyptian study in 2016 which found that the nurses had adequate practice of the professional code of ethics among nurses in outpatient and hemodialysis units (Hafez et al, 2016;Ali et al, 2018). The present study also disagreed with other studies in Iran (2016 and 2023) (Momennasab et al, 2016;Momennasab et al, 2023), Ethiopia (2022) (Haile, 2022) and Indonesia (2020) (Safitri et al, 2020), which found that nurses' adherence to NECP was at a satisfactory level.…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…This study was supported by a study in Gambia (2018) which found that educational level affected the proper practicing code of ethics among nurses (Bah & Sey-Sawo, 2018 However, the current finding was incongruent with the Egyptian study in 2016 which found that the nurses had adequate practice of the professional code of ethics among nurses in outpatient and hemodialysis units (Hafez et al, 2016;Ali et al, 2018). The present study also disagreed with other studies in Iran (2016 and 2023) (Momennasab et al, 2016;Momennasab et al, 2023), Ethiopia (2022) (Haile, 2022) and Indonesia (2020) (Safitri et al, 2020), which found that nurses' adherence to NECP was at a satisfactory level.…”
Section: Discussioncontrasting
confidence: 90%
“…Because of this, nurses could not spend more time with their patients for proper listening and caring for them due to time constraints and heavy workload. Similar results were found in international studies conducted between 2003 to 2022 which revealed that time limitation and shortage in nursing personnel with increasing numbers of patients were the major barriers against proper application of NCEP and quality of nursing care (Bennett et al, 2003;Aliyu et al, 2015;Ghanem et al, 2015;Bah & Sey-Sawo, 2018;Jafarimanesh et al, 2020;Safitri et al, 2020;Asare et al, 2022;Haile, 2022). This similarity proved that barriers to adherence to the NCEP were similar among nurses in different locations around the world.…”
Section: Discussionsupporting
confidence: 73%
“…In Ghana, 69% of nurses experience morally distressing situations with a greater incidence and severity than in other Asian countries (Hoskins et al, 2018 ; Joseph et al, 2022 ). This occurrence can be ascribed to the moral challenges that Ghanaian nurses face related to the cultural and patient factors involving donations of organs, transplants, and palliative or hospice care decisions (Haile, 2022 ; Hoglund et al, 2010 ), and organizational factors, including inadequate resources and insufficient educational training on nursing ethics (Bah & Sey-Sawo, 2018 ; Prompahakul et al, 2021 ). Differing cultural backgrounds can impact moral practices and standards in healthcare (Wright et al, 1997 ).…”
Section: Introductionmentioning
confidence: 99%